HER2, TOP2A, CCND1, EGFR and C-MYC oncogene amplification in colorectal cancer. Issue 7 (1st August 2006) - Al-Kuraya, Khawla; Novotny, Hedvika; Bavi, Prashant; Siraj, Abdul K; Uddin, Shahab; Ezzat, Adnan; Sanea, Nasser Al; Al-Dayel, Fouad; Al-Mana, Hadeel; Sheikh, Salwa S; Mirlacher, Martina; Tapia, Coya; et al.
Abstract : Aim: Recent studies had suggested substantial molecular differences between tumours from different ethnic groups. In this study, the molecular differences between the incidences of colorectal carcinoma in Saudi and Swiss populations are investigated. Method: 518 cases of colon cancer tumours (114 from Saudi Arabia and 404 from Switzerland) were analysed in a tissue microarray format. Fluorescence in situ hybridisation (FISH) was used to estimate frequencies of copy number changes of known oncogenes, including HER2, TOPO2A, CCND1, EGFR and C-MYC. Results: Using FISH, amplifications were mostly low level (gene-to-centromere ratio 2 to 4), which is in contrast with other tumour types with more frequent gene amplifications. The amplifications were particularly frequent for MYC (Saudi 9% and Swiss 14.2%) but unrelated to clinical outcome and pathological information. Remarkably, there were four tumours exhibiting classic high-level gene amplification for HER2 (Swiss 1.3%), a pattern often accompanied by response to trastuzumab (Herceptin) in breast cancer. Occasional high-level amplifications were also observed for CCND1 (Saudi 1/106, 0.9%; Swiss 2/373, 0.5%) and EGFR (Swiss 2/355; 0.6%). Conclusions: Rare high-level amplifications of therapeutic target genes were found in patients with colon cancer. Although no molecular differences were found between incidences of colon cancer cases in Swiss and Saudi populations, these observations emphasise the urgent need for clinical studies investigating the effect of targeted therapies.